2021
DOI: 10.1002/slct.202004444
|View full text |Cite
|
Sign up to set email alerts
|

2‐(Quinol‐8‐yl)pyrrole‐Boron Difluoride Complexes, Simple and Tractable Structures Exhibiting Red Emission

Abstract: The boron difluoride complex bearing 2‐(quinol‐8‐yl)pyrrole as a ligand was synthesized as well as its derivatives bearing aromatic ring substituents at the α‐position of the pyrrole moiety. These compounds showed the potentiality of good red emission character in spite of their simple structures. In the present paper, the details of their optical properties are described and discussed based on computational studies and X‐ray structural analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In our previous report, the 2-(quinol-8-yl)pyrrole-boron complexes exhibited red emissive properties with large Stokes shifts because of their ICT characters and a geometry relaxation effect. 21 This study suggested that the quinoline moiety has significant influence over the optical properties of fluorochromes despite its simple structure. are few reports for other quinolylpyrrole-boron complexes, 22 and their optical properties are not clear.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In our previous report, the 2-(quinol-8-yl)pyrrole-boron complexes exhibited red emissive properties with large Stokes shifts because of their ICT characters and a geometry relaxation effect. 21 This study suggested that the quinoline moiety has significant influence over the optical properties of fluorochromes despite its simple structure. are few reports for other quinolylpyrrole-boron complexes, 22 and their optical properties are not clear.…”
Section: ■ Introductionmentioning
confidence: 99%
“…25 To overcome these limitations, the development of BODIPY analogues remains an active research area. 9,26 Compared to BODIPYs and despite the presence of the pyridine as chelating ligand, which enhances the fluorescent emission properties 27,28,29,30,31,32,33 it is striking to see how little the four-coordinated difluoro dipyridomethene boron complexes, also known as BF2-DIPYRs, has been investigated. Beside the initial synthetic reports, 34,35 the first description of the physical and spectroscopic properties as well as the synthetic diversification of the structure was reported only recently.…”
Section: Introductionmentioning
confidence: 99%
“…S1 and S2 †). In addition, although azine moieties are frequently used as a component of BF 2 complexes, 8,13,16,[23][24][25][26][27][28][29] their systematic study on structure-property relationships has never been reported to the best of our knowledge. In this study, we synthesized 1b with quinoline and 1c with isoquinoline, in which a benzene ring is fused to the pyridine ring of 1a, and fully fused 1d, in which a benzene ring is fused between the pyridine and carbazole moieties of 1a, and clarified the effects of the position of the fused benzene ring with the pyridine ring of 1a on the photophysical and electrochemical properties (Fig.…”
Section: Introductionmentioning
confidence: 99%